O papel do coordenador pedagógico na organização do trabalho escolar no ensino fundamental: um estudo em uma escola municipal, Barcarena Pará - SIMÕES, Luziane Moraes (2019)
The objective of this work is to analyze the role of the pedagogical coordinator, as well as his / her development and resourcefulness towards the students and teachers of the basic education, their competences and deviations of functions before the necessities in the daily work. Aiming to understand the pedagogical practice of the pedagogical coordinator in primary education, through their daily practices, accompanied by the school managers as well as their specific assignments, both with the teaching staff, as well as with the student body that together seek the best way to execute the plans elaborated for a given period will be discussed with Bertolo and Dabul (2013), Libâneo (2005), Queiroz (2003), Ferreira (2004). Franco and Nogueira (2016) The pedagogical Coordinator, accompanied by the schooladministrators, has specific attributions, both with the faculty and with the student body, who together seek the best way to execute the plans elaborated for a given period; which is stated by Bertolo and Dabul (2013, p. 45).